The Relationship Between Personal Hygiene and Skin Disease Symptoms in Scavenger Pickers at The Putri Cempo Landfill Surakarta - Nurlita Buana Jati; Rezania Asyfiradayati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The environmental conditions of the Landfill (TPA) of unhygienic waste are at high risk to the skin health of workers, especially scavengers who interact directly with waste every day. This study aims to analyze the relationship between personal hygiene and symptoms of skin diseases in scavengers at TPA Putri Cempo Surakarta. This research is an analytical observational research design through a cross sectional approach that has been carried out in February 2026 at the Putri Cempo Surakarta Landfill located in Mojosongo Village, Surakarta. Sampling involved 162 respondents obtained from a population of 287 people at the Putri Cempo Landfill through the calculation of the Lemeshow formula and purposive sampling techniques. Primary data was collected through filling out questionnaires and direct observation. The results showed that 78 (80.4%) scavengers with poor personal hygiene had experienced skin diseases in the last six months. The results showed that there was a significant relationship between the incidence of skin diseases and personal hygiene supported by the chi-square test with a p value of 0.028 (p < 0.05). So it can be concluded that poor personal hygiene has an impact on the appearance of skin disease symptoms in scavengers at landfills. Good preventive measures and personal hygiene are the key to increasing the safety and productivity of scavengers.